Management Education through Learning, Motivation, and Personal Independence in Coffee Shop Business Actors - Muhammad Arifin; Muh. Arif; Hilda Apriani; Rita Rita; Sabran Laori; Hinaya Aulia Arifin (Journal La Edusci, 2025)
This study examines the influence of learning, motivation, and personal independence on management education among coffee shop business actors in Makassar, South Sulawesi, a region experiencing rapid growth in café culture and entrepreneurial activity. As small-scale enterprises increasingly occupy a strategic role in Indonesia’s urban creative economy, understanding the behavioral and cognitive determinants that strengthen managerial capacity has become essential. Using a quantitative approach, the research surveyed 120 coffee shop owners and managers selected through purposive sampling, ensuring that respondents possessed adequate managerial exposure and operational experience. Data were collected using a structured, validated questionnaire and analyzed through multiple regression to determine the extent to which each predictor variable contributed to management education outcomes. The results demonstrate that learning, motivation, and personal independence each exert significant positive effects, collectively explaining a substantial proportion of variance in managerial competencies. These findings underscore the importance of continuous learning engagement, intrinsic entrepreneurial motivation, and autonomous decision-making as core components of management development in micro-enterprise settings. The study contributes empirical clarity to management education studies by highlighting the interplay of psychological and experiential factors that shape managerial effectiveness outside formal institutional frameworks. It also offers practical insights for policymakers, training institutions, and industry stakeholders seeking to elevate the capabilities of small business actors through targeted educational interventions. The research concludes by emphasizing the need to integrate experiential, context-sensitive, and behaviorally oriented learning pathways to strengthen the sustainability and competitiveness of coffee shop enterprises.